Leukocyte cell population data (volume conductivity scatter) in postprandial leukocyte activation. Issue 6 (13th May 2013) - Klop, B.; van de, G.‐J. M.; Njo, T. L.; Janssen, H. W.; Rietveld, A. P.; van, A.; Fernández‐Sender, L.; Elte, J. W. F.; Castro Cabezas, M.
Summary Introduction Changes in leukocyte cell population data have been reported in various infectious diseases, but little is known in other inflammatory conditions such as the postprandial state. We investigated whether leukocyte cell population data change during postprandial leukocyte activation. Methods Healthy volunteers underwent a standardized oral fat loading test (OFLT). Flowcytometric quantitation of leukocyte activation markers CD11b, CD66b, CD35, and CD36, together with leukocyte cell population data from LH750 hematology analyzers were measured fasting and at 4 and 8 h postprandially. Results Twelve volunteers were included. Postprandial leukocyte activation was confirmed by increased expression of CD11b by monocytes (+11.7%) and neutrophils (+15.0%) and by increased expression of CD66b (+14.7%) and CD35 (+16.6%) by neutrophils at T = 4 h. The mean scatter from neutrophils, reflecting granularity, significantly decreased at T = 4 h (P < 0.05) and returned to baseline at T = 8 h (P‐anova 0.048). The mean volume of monocytes increased significantly at T = 4 h (P < 0.001) and returned to baseline at T = 8 h (P‐anova 0.0008). At T = 4 h, CD11b expression on neutrophils was associated with a reduction in mean scatter of neutrophils (Pearson's r: −0.677, P = 0.016). Conclusion Postprandial leukocyte activation is accompanied by temporary changes in leukocyte cell population data, similar to changes observed during various infections, but to a lesser extent.